An Improved Two-Dimensional Simplification Calculation Method for Axial Flux Permanent Magnet Synchronous Motor - Hongxue Wu; Yiheng Zhou; Xiaobao Yang (Applied Sciences, 2023)
The axial flux permanent magnet synchronous motor (APMSM) has the advantages of short axial size, high efficiency, and high power density. However, the three-dimensional magnetic circuit structure of this type of motor results in a longer calculation time, which is not conducive to rapid design and optimization. In order to quickly and accurately complete the preliminary calculation and optimization of axial flux permanent magnet synchronous motors, this paper proposes an improved equivalent calculation method for two-dimensional multi-layer linear motors. This method is based on the traditional two-dimensional multi-layer linear motor equivalent method, taking into account the complexity of geometric model establishment and simulation condition settings and applying the principle of analogy to achieve significant simplification of geometric modeling and simulation settings. The article elaborates on the correlation and differences between the proposed method and existing methods and verifies the calculation accuracy through finite element calculation. The results indicate that the improved two-dimensional multi-layer linear motor equivalent calculation method proposed in this article can significantly reduce calculation time while ensuring calculation accuracy and has good application prospects in preliminary design and parameter optimization processes.